El siglo xvi en los lienzos de Coixtlahuaca - Sebastian van Doesburg (Journal de la Société des Américanistes)
The Sixteenth Century in the Coixtlahuaca Lienzos. The three large lienzos painted in the city-state of Coixtlahuaca (Parmenter 1970 ; König 1984) show, among the information on the prehispanic political history, several scenes that represent events ocurring during the early colonial period. These scenes stand out for the appearance of Spanish administrators. In this article, I propose an identification for the people represented in these scenes and I attempt to reconstruct a reason for the inclusion of these scenes in the document.